2008
DOI: 10.2135/cropsci2007.06.0355
|View full text |Cite
|
Sign up to set email alerts
|

Allelic Variation at the Vernalization Genes Vrn‐A1, Vrn‐B1, Vrn‐D1, and Vrn‐B3 in Chinese Wheat Cultivars and Their Association with Growth Habit

Abstract: Information on the distribution of vernalization genes and their association with growth habit is crucial to understanding the adaptability of wheat (Triticum aestivum L.) cultivars to different environments. In this study, 278 Chinese wheat cultivars were characterized with molecular markers for the vernalization genes Vrn‐A1, ‐B1, ‐D1, and ‐B3 Heading time was evaluated in a greenhouse under long days without vernalizaton. The dominant Vrn‐D1 allele showed the highest frequency in the Chinese wheat cultivars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
102
3
13

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(129 citation statements)
references
References 30 publications
11
102
3
13
Order By: Relevance
“…Among modern wheat varieties, the strong Vrn-A1a allele for early flowering is predominant in regions of very cold winters, where spring wheats are planted in the spring. By contrast, the weaker Vrn-B1a and VrnD1a alleles are present at higher frequencies in the Mediterranean climates where spring wheats are planted during the fall (45,59,60). These results provide an example of the selective forces that could have also operated on VRN-D4.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Among modern wheat varieties, the strong Vrn-A1a allele for early flowering is predominant in regions of very cold winters, where spring wheats are planted in the spring. By contrast, the weaker Vrn-B1a and VrnD1a alleles are present at higher frequencies in the Mediterranean climates where spring wheats are planted during the fall (45,59,60). These results provide an example of the selective forces that could have also operated on VRN-D4.…”
Section: Discussionmentioning
confidence: 94%
“…These two lines also differed from the other T. aestivum ssp. sphaerococcum accessions by the presence of the Vrn-D1a allele (SI Appendix, Table S5), which carries a large intron deletion that is associated with a spring growth habit and that is present at high frequency in China (45).…”
Section: Vrn-d4mentioning
confidence: 99%
“…Flowering time is one of the best-studied ecologically significant traits under natural or artificial selection for adaptation of plants to specific natural environments (1,2). However, only a few floweringtime genes that function in adaptation have been identified, and their underlying molecular mechanisms have been elucidated (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Among the flowering genes identified in Arabidopsis, only FRIGIDA and FLOWERING LOCUS C, two pivotal regulators of the vernalization pathway, show molecular hallmarks of natural selection, and the polymorphisms in these genes appear to underlie the extensive natural variation of flowering time for local adaptation (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…Deciphering the molecular mechanisms underlying local adaptation of plants is of great interest not only to plant biologists and evolutionary biologists, but also to crop breeders because it could provide useful guidelines for identifying target genes for selection. In recent decades, several flowering genes involved in local adaptation have been identified, including FRIGIDA and FLOWERING LOCUS C in Arabidopsis; Dwarf8 in maize; Ppd-D1 in wheat (Triticum aestivum); EARLY MATURITY 8 in barley (Hordeum vulgare); vernalization genes VRN1-3 in wheat and barley; and FLOWERING LOCUS T (FT) in sunflower (Helianthus annuus) (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). However, elucidating the adaptive genetic variation in flowering-time control and the underlying molecular mechanisms has remained a challenging task.…”
mentioning
confidence: 99%
“…Common wheat, an allohexaploid, contains three homoeologous copies of VRN1, which are located on the long arms of chromosomes 5A, 5B and 5D, respectively (Yan et al 2003). Allelic variations in the three homoeologous genes (Vrn-A1, Vrn-B1 and Vrn-D1) are the main factors that determine vernalization requirements (Fu et al 2005;Loukoianov et al 2005;Zhang et al 2008). Recently, Zhang et al (2012) found that a single nucleotide variation in the promoter region of Vrn-D1 is associated with the vernalization response in common wheat.…”
Section: Introductionmentioning
confidence: 99%